Pengembangan Modul P5 PPRA Berbasis Kearifan Lokal di Madrasah Ibtidaiyah - Fithriyah, Dewi Niswatul; Sa’diyah, Zumrotus; Faizah, Lyla Nur (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2024)
One of the characteristics of the Independent Curriculum is the existence of the Pancasila Student Profile Strengthening Project and Rahmatan Lil Alamin Student Profile (P5PPRA), which aims to strengthen character and learn from the surrounding environment. P5PPRA activities are carried out by carrying out projects often not following local wisdom. This study aims to develop a P5PPRA module based on local wisdom in Bojonegoro. This study uses the ADDIE development model (analysis, design, development, implementation, evaluation). The results of this study are the development of a P5PPRA module based on local wisdom containing material about Bojonegoro's typical batik, which can equip students to understand local batik and have the skills to make simple batik using the eco print technique. It is evidenced by the percentage of student questionnaire results showing that students' attitudes towards the module reached 90%, and students' interest in the module reached 92%. In addition, the relevance of the module to improving students' batik skills reached 88%.